Pre-lithiated lithium-silicon alloy material arrangements, anodes comprising same, and methods of making material arrangements
Through the use of lithium-silicon alloy materials on the anode electrode of a lithium-ion battery, the pre-lithium surface coating is applied to solve the problem of lithium ion loss during the cycle of lithium ion batteries, which improves the stability and life of the battery.
Patent Information
- Application Number
- CN202380047251.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-14
- Filing Date
- 2023-04-14
- Publication Date
- 2025-01-28
AI Technical Summary
Lithium-ion batteries are susceptible to capacity loss during charging and discharging cycles, especially due to the formation of the SEI layer, which leads to lithium ion loss.
The lithium-silicon alloy material is arranged, and the surface coating is applied to the base of the silicon material, including NA, B, LI, AL, P, O, FE, and/or Ti, to form pre-lithium surface coating Layers to reduce lithium ion losses.
By reducing the loss of lithium ions, extending the cycle life of lithium -ion batteries, and improving the chemical and mechanical stability of the battery.
Smart Images

Figure CN119384730A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a lithium-silicon-alloy material arrangement, a method for manufacturing a surface-coated lithium-silicon alloy material arrangement, an anode electrode, a method for manufacturing at least one anode electrode, and to an electrochemical storage device (electrochemical energy storage device). Background Art
[0002] Lithium-ion batteries are widely used and provide stored energy to different components. In particular, in electric vehicles and hybrid electric vehicles, such lithium-ion batteries supply electrical energy to vehicle components and the drive train. In such use cases, a long electric drive range is very desirable and can be achieved by increasing the capacity of the battery. The capacity of the battery can be increased by increasing the surface area of the electrode. This is achieved by more complex surface structures. Different methods are known for coating at least one of the current collectors of the anode with silicon-carbon in order to increase the area for reversible lithium insertion and the amount of lithium ions involved during the charging and discharging process. For example, such complex surface structures and coatings may be prone to chemical reactions with environmental compounds during the manufacture of lithium-ion batteries. In particular, during the electrolyte filling process of lithium-ion batteries, parts of the anode and its surface structure may be accidentally exposed to harmful substances, such as oxidizing substances.
[0003] Furthermore, lithium-ion batteries are still susceptible to capacity loss over a large number of cycles due to the formation of a solid electrolyte interphase layer (SEI layer). Such an SEI layer is generally formed due to the reduction of organic solvents and anions on the electrode surface during the charge and discharge cycles of the lithium-ion battery. A relevant portion of the SEI layer is formed during the first charge and discharge cycles. Summary of the invention
[0004] The object of the present disclosure is to provide a silicon-alloy material and a method for preparing a silicon-alloy material, which has improved chemical stability, which reduces the lithium loss for forming the SEI layer in the first cycle of the electrochemical device. This object is achieved by the subject matter of the independent claims. Further developments of the subject matter of the independent claims are provided in the dependent claims.
[0005] According to one aspect of the present disclosure, a lithium-silicon alloy material arrangement is provided. Such a lithium-silicon alloy material arrangement can be formed as a surface-coated lithium-silicon alloy material arrangement. In particular, such a lithium-silicon alloy material arrangement can be used in an anode electrode, and thus can be used in an electrochemical storage device such as a lithium-ion battery cell or battery.
[0006] The lithium-silicon alloy material arrangement comprises a silicon material substrate having a silicon content of 30% to 94%, including 30% and 94%. In addition, the lithium-silicon alloy material arrangement contains at least one additional element, in particular additional elements such as Na, C, B, Al, Fe, Ni, Ti. In addition, the lithium-silicon alloy material arrangement comprises a Li content of 3% to 25%, including 3% and 25%. Therefore, the lithium-silicon alloy material arrangement is provided in a pre-lithiated form, wherein at least one surface coating layer of the surface coating may contain lithium ions. The silicon content and the lithium content may be defined relative to the weight / mass or volume of the entire silicon-carbon composite material.
[0007] The lithium-silicon alloy material arrangement also includes a surface coating applied at least partially on a surface area of the lithium-silicon alloy material arrangement. The surface coating includes at least one first surface coating layer comprising one or more elements of Na, B, Li, Al, Si, P, O, Fe and / or Ti.
[0008] Depending on the preferred application, the lithium-silicon alloy can be present as a first surface coating layer on a silicon material substrate or on the top of a silicon base material. This material can be provided as a plurality of particles, which are coated individually or in groups with a lithium-silicon alloy material as a first surface coating layer.
[0009] In another aspect of the present invention, an anode electrode comprising a surface-coated lithium-silicon alloy material arrangement is provided. The anode electrode may preferably include a current collector, such as a metal foil. On one or both sides of the current collector, a lithium-silicon alloy material arrangement may be provided to improve the electrical properties of the anode electrode.
[0010] By providing at least one surface coating, for example, a first surface coating layer, the chemical and mechanical stability of the surface-coated lithium-silicon alloy material arrangement and thus the anode electrode having such a material is improved. In particular, the surface coating can be applied via chemical vapor deposition, such as an atomic layer deposition method, or via chemical vapor infiltration. Such a surface coating can also be applied to materials with complex or uneven surface geometries.
[0011] Due to the introduction of lithium into the surface-coated lithium-silicon alloy material arrangement, lithium loss during the formation of the SEI layer during the first charge and discharge cycle in an anode electrode having such a material is prevented or minimized. The SEI layer is generally formed due to the reduction of organic solvents and anions on the anode electrode surface during the charge and discharge cycles of an electrochemical cell. Since such organic solvents and anions are not present in the pre-lithiated lithium-silicon alloy material arrangement, SEI layer formation is minimized.
[0012] When the at least partially applied first surface coating is formed as a layer having a thickness of 0.2 μm to 3 μm, lithium ions for reversible lithium intercalation can bypass the first surface coating without a significant decrease in corresponding kinetics.
[0013] According to another embodiment, the first surface coating layer and / or the second surface coating layer include at least one metal alloy from at least one or more of Li, Na, B, Al, Si, P, Fe and / or Ti. For example, suitable metal oxides can be formed as Al2O3 and / or LiAlO2.
[0014] In another embodiment, the surface coating covers at least 50% of the surface area of the lithium-silicon alloy material arrangement. Thus, most of the surface area of the material can be protected by the surface coating. The surface area of the lithium-silicon alloy material arrangement is defined as the entire surface area applied to the anode electrode in its final form. Thus, all or most of the surface of the lithium-silicon alloy material arrangement that is not in contact with the current collector foil of the anode electrode can include the surface coating.
[0015] The surface coating of lithium-silicon alloy material arrangement can include multiple surface coating layers, and these surface coating layers can also at least partially cover the available surface area of silicon-carbon composite material.Different surface coating layers can overlap each other at least partially.Therefore, based on another embodiment, the surface coating of lithium-silicon alloy material arrangement includes a second surface coating layer.According to requirements and preferred manufacturing method, the second surface coating layer is applied to the top of the first surface coating layer, or the first surface coating layer is applied to the top of the second surface coating layer.The second surface coating layer makes it possible to control the chemical and mechanical stability of lithium-silicon alloy material arrangement in addition.
[0016] In another embodiment, the surface coating includes a third layer for passivation, especially formed as a carbon coating. When the material is used in an electrode, such a third surface coating layer can cause the resistance of the material in the transition region between the second surface coating layer and the current collector or metal to decrease. In addition, this passivation layer can increase the conductivity within the layer of the silicon-carbon composite material. In another embodiment, by flushing a dry atmosphere (O2, N2 or a mixture thereof) on the silicon-carbon composite material at an elevated temperature between 120°C and 250°C, additional steps can be applied to further passivate the surface region or the silicon-carbon composite material.
[0017] In another embodiment, the surface area (surface area, surface area) of the lithium-silicon alloy material arrangement is less than 20m2 / g. Therefore, the first surface coating layer and / or the second surface coating layer can be effectively applied to the material with increased surface area due to its porous carbon support. The surface area can be measured according to the BET measurement method.
[0018] According to another aspect of the present invention, a method for manufacturing a surface-coated lithium-silicon alloy material arrangement is provided. In the method steps, a silicon material substrate with a silicon content of 30 to 99.5% is provided. In addition, a Li or Na compound is applied to the surface area of the silicon material substrate. At least one other compound comprising Si, Fe, Ni, and / or Ti is applied to the surface area of the silicon material substrate to provide a chemical reaction with the Li compound, thereby forming a first surface coating layer. Therefore, pre-lithiation of the material is provided via the first surface coating layer. At least one other compound can be applied via chemical vapor infiltration, therefore, a lithium-silicon alloy material can be formed, wherein the lithium-silicon alloy material can be formed as the first surface coating layer coating the silicon material substrate or substrate particles.
[0019] In another step, at least one second surface coating is applied at least in part.At least one second surface coating comprises a mixture of lithium oxide or silicon oxide or aluminum oxide or zirconium oxide or niobium oxide or tungsten oxide or above-mentioned oxides.After providing the above steps, the lithium-silicon alloy material arrangement of surface coating is formed.Preferably, the application of the first surface coating and the application of the second surface coating can be carried out in any order.Therefore, the first surface coating can be applied or formed initially or after forming the second surface coating.
[0020] By providing a surface coating comprising silicon oxide or aluminum oxide or zirconium oxide, the lithium-silicon alloy material can be protected against unintended chemical reactions, such as uncontrolled oxidation processes. In particular, when manufacturing a battery cell or electrochemical storage device, an electrode comprising a surface-coated silicon-carbon composite material will provide improved chemical stability and a reduced likelihood of undesired chemical reactions due to at least partial surface coating.
[0021] In order to introduce lithium into the first surface coating layer, the Li or Na compound is applied as LiAlH4 or NaBH4 and introduced onto the surface of the silicon material substrate via a solution-based method or via a dry coating method. For example, after heating the resulting material, for example, at 450°C, the solvent can be removed and gaseous byproducts such as CH4 and H2 can also evaporate. Therefore, only the Li ions of LiAlH4 can remain. Alternatively, LiAlH4 is introduced into the surface area of the silicon material substrate in the form of a dry coating, for example via calendering.
[0022] Based on the application and requirements, the Li compound can be formed as LiBH4, NaBH4 and / or LiFePO4.
[0023] In another embodiment of the method, at least one third surface coating layer is applied to form a passivation layer. The third surface coating layer can be formed as a carbon layer. Alternatively or additionally, oxygen or a mixture comprising oxygen and nitrogen can be introduced to form SiO2 as a passivation, protective layer.
[0024] Furthermore, at least one further compound is applied as silane (SiH 4 ) after applying LiAlH 4 . Thus, LiAlH 4 and SiH 4 can react with Li—Al—Si, while forming H 2 which can be dissipated.
[0025] In one embodiment, the at least one second surface coating layer of the surface coating of the silicon material substrate is applied via a vapor deposition method. Thus, methods such as atomic layer deposition or molecular layer deposition can be performed to provide a surface coating with a controlled and uniform layer thickness.
[0026] According to one embodiment, at least one second surface coating layer is at least partially applied to the surface area of the silicon material substrate by mixing the silicon material substrate with a compound of at least one or more of the elements Li, Na, Fe, B, Al, P, Ti, Zr, Nb, and W.
[0027] According to another embodiment, the second surface coating layer of the surface area of the silicon material substrate comprises at least one metal oxide from at least one of the elements B, Al, Si, Zr, Nb, W and / or Li. Thus, in the case of atomic layer deposition or molecular layer deposition, metal oxides are used as precursors.
[0028] Alternative or additional precursors may be formed of ZrO2, TiO2, Al2O3, SiN x 、TaN x Etc. In addition, molecules such as Nb(OEt)5 or Li-N(SiMe3)2 can be introduced to precisely control the chemical composition of at least one surface coating. Thus, the method for manufacturing a surface-coated lithium-silicon alloy material arrangement includes a variety of possible materials for adjusting the chemical and mechanical properties of the surface coating.
[0029] In another embodiment, suitable metal oxides may be formed as ZrO2 or / and Li2ZrO3 or a mixture of Al2O3, ZrO2 and mixed lithium aluminum oxide and lithium zirconium oxide.
[0030] Suitable surface coatings may be applied via an atomic layer deposition (ALD) process of trimethylaluminum with water or oxygen at a temperature between 100°C and 450°C (followed by two or more ALD cycles), optionally followed by a chemical reaction of the resulting aluminum oxide and aluminum hydroxide with a lithium compound such as Li-N(SiMe3)2 to form a lithiated metal oxide. Such coatings may also be applied in combination with thermal exposure and / or in combination with a catalyst. In another embodiment, the surface coating may be applied by mixing a metal oxide compound (Al2O3, Zr(OH)4, ZrO(OH)2 with a lithium compound followed by a thermal treatment step at a temperature above 200°C.
[0031] In another embodiment, a method is provided, wherein a surface region of a silicon material substrate or a surface region of a first surface coating layer is treated with a metal alkoxide or a metal amide or an alkyl metal compound to form a treated compound layer on the surface region; and wherein the treated compound layer on the surface region is treated with moisture or oxygen or ozone to form at least one second surface coating layer.
[0032] According to another embodiment, the surface area of the silicon material substrate or the surface area of the first surface coating layer is treated with a metal alkoxide or a metal amide or an alkyl metal compound to form a treated compound surface, and the treated compound surface is treated with moisture or oxygen or ozone. Thus, it is possible to ensure that a uniform coating of the surface area of the lithium-silicon alloy material is formed without leaving any unwanted traces of the treated compound, such as AlCH3.
[0033] In another embodiment, at least one surface coating of lithium-alloy-carbon material or lithium-silicon-carbon composite material is processed with metal alkoxide or metal amide or alkyl metal compound, to form treated compound surface on the surface area of silicon-carbon composite material, wherein treated compound surface is processed with moisture or oxygen or ozone, to form at least one layer of first surface coating layer. Such material for forming treated compound surface is widely used, and therefore can be provided in a cost-effective manner. For example, trimethylaluminum can be utilized to form treated compound surface.
[0034] In another embodiment, at least one surface coating layer of the surface area of the lithium-silicon alloy material arrangement is formed to have a lithium content. Thus, by providing lithium, for example, as LiAlO2 in addition to Al2O3, a molecular pathway for faster lithium ion exchange between the electrolyte and the silicon-carbon composite material of the electrode can be introduced. Preferably, the lithium can be introduced into the surface coating of the surface area of the silicon material substrate and / or into the silicon material substrate.
[0035] The manufacturing method can be accelerated if at least one first surface coating layer and / or at least one second surface coating layer are applied to the surface area of the silicon material substrate at a temperature in the range of 150° C. to 450° C. Such method steps can be carried out in a protective atmosphere such as, for example, nitrogen or an inert gas.
[0036] According to another embodiment, the silicon material substrate or the first surface coating layer is treated with a metal alkoxide or a metal amide or an alkyl metal compound to form a treated compound surface and the treated compound surface is treated with moisture or oxygen or ozone. Thus, it is possible to ensure that a uniform coating of the surface area where the lithium-silicon alloy material is arranged is formed without leaving any unwanted traces of the treated compound, such as AlCH3.
[0037] According to another aspect of the present invention, a method for manufacturing at least one anode electrode is provided. In one step, a current collector is provided. In addition, the surface-coated lithium-silicon alloy material of the present invention is arranged at least partially on at least one side of the current collector.
[0038] According to another aspect of the present invention, a method for manufacturing at least one anode electrode is provided. In one step, a silicon material, especially a surface-coated lithium-silicon alloy material, is arranged and mixed with at least one carbon material. The silicon material is combined with an aqueous binder solution and / or a non-aqueous binder solution to form an electrode slurry. The electrode slurry is applied to a current collector, such as a conductor foil. The current collector with the applied electrode slurry is dried at a temperature of 100° C. to 140° C. to form at least one anode electrode. The current collector can be formed as a foil made of a conductive material.
[0039] As the binder, a styrene-butadiene gum / carboxymethyl cellulose (CMC / SBR) blend, polyacrylic acid (PAA) and / or lithium polyacrylate (LiPAA) or sodium polyacrylate (NaPAA) can be used. In an alternative embodiment, the binder is formed as a fluoropolymer, such as polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), polyethylene tetrafluoroethylene (ETFE), polyvinyl fluoride (PVF), polyethylene trifluorochloroethylene (ECTFE), (polyvinylidene fluoride (PCDF), (polytrifluorochloroethylene (PCTFE), trifluoroethanol or a combination of at least one of these materials and at least one other material. In another embodiment, the binder is a copolymer of polyimide or polyacrylic acid and styrene-butadiene. Other possible binders can be formed as methyl methacrylate or polyvinylidene fluoride.
[0040] Depending on the preferred application, according to another aspect of the present invention, the method for manufacturing the anode electrode can also be performed based on a dry or semi-dry lithium-silicon alloy material arrangement mixture.
[0041] In a first step, a dry silicon material substrate is combined with a binder powder and includes providing graphite particles and / or carbon black particles. The binder powder may be formed as a PTFE powder.
[0042] Optionally, 5% to 10% ethylene carbonate may be added to the mixture.
[0043] The resulting mixture in combination with the binder powder is then at least partially applied to at least one surface of a conductor foil or a current collector via calendering. In a further step, at least one surface coating is applied to the surface region of the silicon-carbon composite material to form a surface-coated lithium-silicon alloy material arrangement, wherein the at least one surface coating comprises aluminum oxide or zirconium oxide and at least partially covers the surface region of the lithium-silicon alloy material arrangement.
[0044] The conductor foil with the applied dried or semi-dried electrode slurry is then dried at a temperature of, for example, 100° C. to 140° C. to form at least one anode electrode.
[0045] In another aspect of the invention, an electrochemical storage device is provided, in particular formed as a lithium ion battery or lithium ion battery cell. The electrochemical storage device comprises at least one anode electrode of the invention, at least one cathode electrode, a separator arranged between the cathode electrode and the anode electrode, and an electrolyte containing lithium ions. The cathode electrode preferably comprises a transition metal oxide. Preferably, the components of the electrochemical storage device are positioned in a housing or box, such as an aluminum bag.
[0046] By utilizing an anode electrode having a surface-coated lithium-silicon alloy material arrangement, the requirements for a dry room environment for manufacturing an electrochemical storage device may be reduced due to the surface-protected anode electrode.
[0047] In another aspect of the present invention, there is provided use of an anode electrode in an electrochemical storage device of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] The present disclosure will be described in more detail below based on the exemplary embodiments shown in the accompanying drawings:
[0049] Figure 1 An exemplary diagram showing a method for manufacturing a surface-coated lithium-silicon alloy material arrangement according to one embodiment of the present invention;
[0050] Figure 2 An exemplary electrochemical storage device having a fabricated electrode anode including a surface-coated lithium-silicon alloy material arrangement is shown, and
[0051] Figure 3An exemplary electrochemical storage device having a fabricated electrode anode including a surface-coated lithium-silicon alloy material arrangement is shown according to another embodiment. DETAILED DESCRIPTION
[0052] In the drawings, the same reference numerals indicate similar elements. The sizes and relative positions of the elements in the drawings are not necessarily drawn to scale, and some of these elements are enlarged and positioned to improve the legibility of the drawings. Further, the specific shapes of the drawn elements are not intended to convey any information about the actual shape of the specific elements, and are selected only for ease of identification in the drawings.
[0053] Unless the context requires otherwise, throughout this specification and claims, the word "comprise" and variations thereof (such as "comprises" and "comprising") are to be interpreted in an open, inclusive sense, i.e., as "including, but not limited to". In this specification, unless otherwise indicated, any concentration range, percentage range, ratio range, or integer range is to be understood to include the value of any integer within the range, and, where appropriate, fractions thereof (such as tenths and hundredths of integers). As used herein, the terms "about" and "approximately" refer to ±20%, ±10%, ±5%, or ±1% of the indicated range, value, or structure, unless otherwise indicated. It should be understood that the terms "a" and "an" as used herein refer to "one or more" of the listed components. The use of alternatives (e.g., "or") is to be understood to refer to one, two, or any combination thereof of the alternatives.
[0054] References throughout this specification to "one embodiment" or "an embodiment" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment is included in at least one embodiment of the present disclosure. Thus, the phrases "in one embodiment" or "in an embodiment" appearing in various places throughout this specification do not necessarily all refer to the same embodiment. Furthermore, the particular features, structures, or characteristics may be combined in any suitable manner in one or more embodiments.
[0055] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs. As used in the specification and claims, the singular forms "a", "an", and "the" include plural references unless the context clearly dictates otherwise.
[0056] The carbon part of the term silicon-carbon composite material refers to a material or substance consisting of carbon or at least containing carbon. In this regard, the carbon material can include high purity, amorphous and crystalline materials. The carbon material can be activated carbon, pyrolyzed dry polymer gel, pyrolyzed polymer cryogel, pyrolyzed polymer xerogel, pyrolyzed polymer aerogel, activated dry polymer gel, activated polymer cryogel, activated polymer xerogel, activated polymer aerogel, or a combination thereof. In another embodiment, carbon can be produced by pyrolysis of coconut shells or other organic wastes. In this regard, a polymer is a molecule comprising two or more repeating structural units. Porous carbon, also referred to as porous carbon material, provides advantages of being generally easy to produce, generally having low impurities and large pore volume. Therefore, porous carbon exhibits good electrical conductivity and high mechanical and chemical stability. In one embodiment, the carbon material has a high micropore volume ratio. Typically, porous carbon has a pore space, also referred to as a pore volume, wherein the pore space is a group of voids (pores) in carbon that can be filled with a gas or fluid. To this end, the properties and methods of making porous carbon are disclosed in the prior art (e.g., U.S. Publication No. 2017 / 0015559), the entire disclosure of which is incorporated herein by reference in its entirety for all purposes.
[0057] The Si portion of the silicon-carbon composite material may be pure silicon or a material composition containing silicon. For example, the Si portion may be at least one alloy. The alloy may be a silicon-titanium alloy (Si-Ti), a silicon-iron alloy (Si-Fe), a silicon-nickel alloy (Si-Ni). In another embodiment, the Si portion may be composed of a P dopant, an As dopant, or an N dopant. The P dopant is typically a phosphorus dopant, the As dopant is typically an arsenic dopant, and the N dopant is typically a nitrogen dopant.
[0058] For example, the surface area of the silicon-carbon composite material is determined by thermogravimetric analysis to determine its silicon content. The silicon-carbon composite material can also be tested in a half-cell button cell. The anode for an exemplary half-cell button cell may contain 60-90% of a silicon-carbon composite material, 5-20% of Na-CMC (as a binder), and 5-20% of Super C45 (as a conductivity enhancer), and the electrolyte may, for example, contain 2:1 ethylene carbonate, diethylene carbonate, 1M LiPF6, and 10% of fluoroethylene carbonate. The half-cell button cell can be cycled for 5 cycles at a rate of C / 5 at 25°C, and then cycled at a rate of C / 10. The voltage can be cycled between 0V and 0.8V, alternatively, the voltage can be cycled between 0V and 1.5V. From the half-cell button cell data, the maximum capacity can be measured, as well as the average coulombic efficiency (CE) in the cycle range from the 7th cycle to the 20th cycle.
[0059] Figure 1An exemplary diagram illustrating a method 1 for preparing a surface-coated lithium-silicon alloy composite material 10 according to one embodiment of the present invention is shown. In the illustrated embodiment, the lithium-silicon alloy material arrangement 10 is formed as a silicon material substrate 20 surface-coated with a Li-Al-Si material as a first surface coating layer 21.
[0060] In a first exemplary method step 2 , a silicon material substrate 20 having a silicon content of 30 to 99.5% is provided. Then, in a further method step 3 , a Li compound 21 is applied to a surface region of the silicon material substrate 20 .
[0061] The Li compound 21 is applied as LiAlH4 and introduced onto the surface of the silicon material substrate 20, for example via a solution-based method or via a dry coating method. For example, after applying LiAlH4 via a solution-based method, the Li compound 21 can be heated, for example, to 450°C, so that the solvent and possible gaseous byproducts such as CH4 and H2 can evaporate. In the described embodiment, in a further step 4, a further compound is applied to the Li compound 21, which is formed as a coating of the silicon material substrate 20.
[0062] After applying LiAlH 4 , at least one other compound is applied as silane SiH 4 . Therefore, LiAlH 4 and SiH 4 can react with Li-Al-Si to form dissipative H 2 simultaneously. This reaction forms a first surface coating layer 22 , which is formed as at least one Li-Al-Si layer. The first surface coating layer 22 is the part of the surface coating 11 of the silicon material substrate 11 .
[0063] In another embodiment of the method, at least one third surface coating layer is applied to form a passivation layer. The third surface coating layer can be formed as a carbon layer. Alternatively or additionally, oxygen or a mixture comprising oxygen and nitrogen can be introduced to form SiO2 as a passivation, protective layer.
[0064] Thus, the first surface coating layer 22 can act as a pre-lithiation of the silicon material substrate 20. The at least one additional compound can be applied by chemical vapor infiltration, and the method step 4 forms a lithium-silicon alloy material arrangement 10, which includes a surface coating 11, wherein the first surface coating layer 22 coats the silicon material substrate 20 as the entire material or substrate particles of the silicon substrate material 20.
[0065] The silicon base material 20 may include different particles and compounds, and may also be formed into compounds to meet specific requirements regarding its application, such as in battery cell applications.
[0066] In the following method steps 5, 6, a second surface coating layer 23 is applied at least partially on the surface area of the first surface coating layer 22. A silicon material substrate 20 having an applied first surface coating layer 22 formed as a Li-Al-Si material as a lithium-silicon alloy material is provided and used as a basis for thermal atomic layer deposition to form the second surface coating layer 23.
[0067] Preferably, the second surface coating layer 23 may contain one or more elements from the group consisting of Li, Na, Al, Zr, Nb, and W.
[0068] The lithium-silicon alloy material of the first surface coating layer 22 is treated with a metal alkoxide or a metal amide or an alkyl metal compound to form a treated compound layer (not shown). In the illustrated embodiment, the surface region of the lithium-lithium-silicon alloy material 22 is covered with trimethylaluminum TMA. During the exposure of the surface region to trimethylaluminum, it dissociatively chemisorbs on the surface region of the lithium-silicon alloy material 22, and any remaining trimethylaluminum in the gas phase can be easily removed.
[0069] The dissociative chemisorption of trimethylaluminum TMA produces a treated compound surface covered with AlCH3 molecules. The treated compound surface is treated with water H2O or oxygen O2 or ozone O3 to form at least one second surface coating layer 23 of the surface coating 11.
[0070] The second surface coating layer 23 consists of Al2O3 molecules, since the treatment results in a chemical reaction of CH3 at the surface of the treated compound. Such a coating can be provided by thermal atomic layer deposition (which also requires increased temperatures, for example above 250°C).
[0071] In an optional method step 7, a third surface coating layer 24 can be applied on top of the second surface coating layer 23. In the embodiment shown, the third surface coating layer 24 is formed as a passivation layer and consists of a carbon material.
[0072] The first surface coating layer 22 , the second surface coating layer 23 , and the third surface coating layer 24 form the surface coating layer 11 of the lithium-silicon alloy material arrangement 10 .
[0073] Figure 2 Shown is a Figure 1 A cross-sectional view of an exemplary electrochemical storage device 100 showing an electrode anode 110 of a surface-coated lithium-silicon alloy material arrangement 10 prepared by the method shown.
[0074] The electrochemical storage device 100 is formed as a lithium-ion battery cell. The electrochemical storage device 100 includes at least one anode electrode 110, at least one cathode electrode 120, and a separator 130 disposed between the cathode electrode 120 and the anode electrode 110. The cathode electrode preferably contains a transition metal oxide.
[0075] In addition, an electrolyte 140 containing lithium ions is provided in the battery cell housing 150 of the electrochemical storage device 100. The electrochemical storage device 100 may be formed as a lithium ion battery cell in a bag form. Therefore, the battery cell housing 150 may be formed as an aluminum bag. The anode electrode 110, the cathode electrode 120 and the separator 130 are also arranged in the battery cell housing 150.
[0076] It should be noted that Figure 2 A simplified cross-sectional view is shown. The anode electrode 110, cathode electrode 120 and separator 130 are typically formed in multiple layers that are rolled or folded to optimize packaging and to increase the possible surface area of the electrolyte 140. In the illustrated embodiment, only one layer of the components is visible for illustration purposes.
[0077] The anode electrode 110 is coated on both sides with a surface coated lithium-silicon alloy material arrangement 10. The surface coating 11 of the surface coated lithium-silicon alloy material arrangement 10 is achieved on surface areas of the lithium-silicon alloy material arrangement 10 that are not in contact with the current collector 111 of the anode electrode 110.
[0078] By utilizing the anode electrode 110 with the surface-coated lithium-silicon alloy material arrangement 10, the requirements for the dry room environment for manufacturing the electrochemical storage device 100 can be reduced. In particular, during the process of filling the electrolyte 140 into the battery cell housing 150, chemical interactions of the electrode anode with contaminants can be reduced or prevented due to the surface protection by the surface coating 11.
[0079] exist Figure 3 , another exemplary electrochemical storage device 100 is shown. The electrochemical storage device 100 includes an electrode anode 110 having a surface-coated lithium-silicon alloy material arrangement 10. Figure 2 Compared to the embodiment shown in , the surface coating 11 of the lithium-silicon alloy material arrangement 10 is partially applied to the surface area of the lithium-silicon alloy material arrangement 10 , so that a partial surface area of the lithium-silicon alloy material arrangement 10 remains without the surface coating 11 .
Claims
1. A lithium-silicon alloy material arrangement (10), in particular formed as a surface-coated lithium-silicon alloy material, comprising: - a silicon material substrate (20) having a silicon content of 30% to 94%, inclusive; and comprising at least one additional element, in particular an additional element such as Na, C, B, Al, Fe, Ni, Ti; - Li content of 3% to 25%, inclusive; - and a surface coating (11) applied at least partially on a surface area of the silicon material substrate (20), wherein the surface coating (11) comprises at least one first surface coating layer (22), wherein the at least one first surface coating layer comprises one or more elements of Li, Na, B, Al, Si, P, O, Fe and Ti, wherein The at least one first surface coating layer (22) comprises a metal alloy from at least one of the elements Li, Na, B, Al, Si, P, Fe and / or Ti.
2. The material arrangement according to claim 1, wherein: The at least one first surface coating layer (22) of the surface coating (11) has a layer thickness in the range of 0.2 μm to 3 μm.
3. A material arrangement according to claim 1 or 2, wherein: The second surface coating layer (23) comprises a metal alloy and a metal oxide, wherein the metal alloy and the metal oxide are from at least one of the elements Li, Na, B, Al, Si, P, Fe, Ti, Nb, Zr and / or W.
4. A material arrangement according to any one of claims 1 to 3, wherein: At least 50% of the surface area of the lithium-silicon alloy material arrangement (10) is covered with the surface coating (11).
5. A material arrangement according to any one of claims 1 to 4, wherein: The surface coating (11) of the lithium-silicon alloy material arrangement (10) comprises a second surface coating layer (23), wherein the second surface coating layer (23) is applied on top of the first surface coating layer (22), or wherein the first surface coating layer (22) is applied on top of the second surface coating layer (23).
6. A material arrangement according to any one of claims 1 to 5, wherein: The surface coating (11) comprises a third layer (24) for passivation, for example, formed as a carbon coating.
7. A material arrangement according to any one of claims 1 to 6, wherein: The surface area of the lithium-silicon alloy material arrangement (10) is less than 20 m 2 / g.
8. A method (1) for producing a surface-coated lithium-silicon alloy material arrangement (10) according to any one of claims 1 to 7, wherein: - providing a silicon material substrate (20) having a silicon content of 30 to 99.5%; - applying a Li compound or a Na compound (21) onto the surface area of the silicon material substrate (20); and - applying at least one additional compound including Si, Fe, Ni, and / or Ti onto the surface region of the silicon material substrate (20) to provide a chemical reaction with the Li compound to form a first surface coating layer (22); as well as - at least partially applying at least one second surface coating layer (23), wherein the at least one second surface coating layer (23) contains lithium oxide or silicon oxide or aluminum oxide or zirconium oxide or niobium oxide or tungsten oxide or a mixture of the above oxides.
9. The method according to claim 8, wherein: The Li compound or Na compound (21) is applied as LiAlH4 or NaBH4 and introduced onto the surface of the silicon material substrate (20) via a solution-based method or via a dry coating method.
10. The method according to claim 8 or 9, wherein: At least one third surface coating layer (24) is applied to form a passivation layer.
11. The method according to any one of claims 8 to 10, wherein: At least one further compound is applied as silane (SiH4).
12. The method according to any one of claims 8 to 11, wherein: At least one second surface coating layer (23) is at least partially applied to the surface area of the silicon material substrate (20) via a vapor deposition method.
13. The method according to any one of claims 8 to 11, wherein: At least one second surface coating layer (23) is at least partially applied to the surface area of the silicon material substrate (20) by mixing the silicon material substrate (20) with at least one or more compounds from the elements Li, Na, B, Al, P, Ti, Fe, Zr, Nb, W.
14. The method according to any one of claims 8 to 13, wherein: The second surface coating layer (23) of the surface region of the silicon material substrate (20) comprises at least one metal oxide from at least one of the elements Li, B, Al, Si, Zr, Nb and W.
15. The method according to any one of claims 8 to 14, wherein: The surface area of the silicon material substrate (20) or the surface area of the first surface coating layer (22) is treated with a metal alkoxide, a metal amide or an alkyl metal compound to form a treated compound layer on the surface area; and wherein the treated compound layer on the surface area is treated with moisture or oxygen or ozone to form the at least one second surface coating layer (23).
16. The method according to any one of claims 8 to 15, wherein: Lithium is introduced into a surface coating (11) in a surface region of the silicon material substrate (20) and / or into the silicon material substrate (20).
17. The method according to any one of claims 8 to 16, wherein: At least one first surface coating layer (22) and / or at least one second surface coating layer (23) are applied to the surface area of the silicon material substrate (20) at a temperature in the range of 150°C to 450°C.
18. The method according to claim 15, wherein: The steps of treating the silicon material substrate (20) or the first surface coating layer (23) with a metal alkoxide, a metal amide or an alkyl metal compound to form a treated compound layer and treating the treated compound layer with moisture, oxygen or ozone are repeated at least once.
19. An anode electrode (110) comprising a current collector (111) and a surface-coated lithium-silicon alloy material arrangement (10) according to any one of claims 1 to 7, wherein: The surface-coated lithium-silicon alloy material arrangement (10) is at least partially arranged on at least one side of the current collector (111).
20. A method for producing at least one anode electrode (110) according to claim 19, wherein - mixing a silicon material, in particular a surface-coated lithium-silicon alloy material arrangement (10), with at least one carbon material, - combining the silicon material with an aqueous binder solution and / or a non-aqueous binder solution to form an electrode slurry, - applying the electrode slurry to a current collector, such as a conductor foil, - Drying the current collector with the applied electrode slurry at a temperature of 100° C. to 140° C., thereby forming at least one anode electrode.
21. An electrochemical storage device (100), in particular in the form of a lithium-ion battery, comprising: - at least one anode electrode (110) according to any one of claims 19; - at least one cathode electrode (120) comprising a transition metal oxide; - a separator (130) disposed between the cathode electrode (120) and the anode electrode (110); and - An electrolyte (140) containing lithium ions.
Citation Information
Patent Citations
Novel methods for sol-gel polymerization in absence of solvent and creation of tunable carbon structure from same
US20170015559A1